Experimental and numerical studies on efficiency characterization of firefighters' protective clothing: a review. Issue 11 (26th October 2022) - Shakeriaski, Farshad; Ghodrat, Maryam; Nelson, David James
Abstract: A review of recent articles on the design of Firefighting Protective Clothing (FFPC) is presented in this work, with the aim of assessing the impact of different efficiency criteria with respect to the design of such clothing. Firefighters often work in risky and extreme environments involving high heat exposure, and therefore protective fabrics are essential to ensure their health and safety is maintained. This need has resulted in numerous studies in the area of FFPCs in the last two decades. A summarized review of existing studies and improvements in FFPC design is presented in this article. Numerical and empirical techniques are reviewed with a focus on the heat transfer properties of FFPC. The impact of air gaps and moisture on FFPC performance are also discussed, along with the use of phase change materials as a promising technology in FFPC design. The limitations of existing designs and further avenues of investigation are outlined.